Implementing asset management : a practical guide. (Association of Metropolitan Water Agencies : National Association of Clean Water Agencies : Water Environment Federation, 2007)
Faced with the challenges of aging infrastructure, the lack of funding, and the desire to maintain affordable rates, while meeting the customer's needs, utility managers are looking for more effective ways to make decisions about capital improvement and infrastructure maintenance. This book provides utility professionals a step-by-step guide to continued improvement in the management of their infrastructure assets. The concepts and processes presented are applicable to utilities of all sizes. Depending on the availability of resources, utilities can address their infrastructure assets at a broad, system-wide level by grouping assets or drill-down to individual assets components and elements.